2020
DOI: 10.1186/s13613-020-00747-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment variables associated with outcome in emergency department patients with suspected sepsis

Abstract: Background Early treatment is advocated in the management of patients with suspected sepsis in the emergency department (ED). We sought to understand the association between the ED treatments and outcome in patients admitted with suspected sepsis. The treatments studied were: (i) the time to antibiotics, where time zero is the time the patient was booked in which is also the triage time; (ii) the volume of intravenous fluid (IVF); (iii) mean arterial pressure (MAP) after 2000 ml of IVF and (iv) the final MAP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
8
0
3
Order By: Relevance
“…The emergency department (ED) is often the first medical contact of patients with sepsis [3], but the medical conditions available are often quite limited. Therefore, the rapid screening of septic patients and identification of critically ill patients is a challenge that needs to be urgently addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The emergency department (ED) is often the first medical contact of patients with sepsis [3], but the medical conditions available are often quite limited. Therefore, the rapid screening of septic patients and identification of critically ill patients is a challenge that needs to be urgently addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid therapy, which is a cornerstone in the treatment of sepsis and associated with outcome in emergency department patients, is commonly used to restore and maintain patients' tissue perfusion [9][10][11]. For many years, the types of fluid administration regarding "crystalloids" and "colloids" is under the heated debate [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…If shock is not present or the patient could have another condition, the recommendation is to perform investigations and if found to have an infection or sepsis, to deliver antibiotics within 3 h of recognition. We too have previously found that the time to antibiotics is critical in those with refractory hypotension, with a number needed to treat of four, but not in those without refractory hypotension ( 28 ). We have also suggested that a SBP of <100 mmHg could be used to identify patients who are likely to develop refractory hypotension.…”
Section: Discussionmentioning
confidence: 99%